Características sociodemográficas, creencias y nivel de motivación de donantes voluntarios del centro Hemodador Regional de Loreto-banco de sangre tipo II – 2025 - Urrelo Valcarcel, Diego Alejandro (2025)
The objective of this research was to analyze the relationship between sociodemographic characteristics, personal beliefs, and the level of motivation among voluntary blood donors at the Regional Hemodador Center – Type II Blood Bank in Loreto, in 2025. A quantitative approach was used, with a descriptive, cross-sectional, and prospective design. A sample of 387 voluntary donors completed structured surveys. The analysis included descriptive statistics, chi-square tests, and Spearman’s correlation. Results showed that most voluntary donors were male (64.9%), single (67.7%), between 18 and 25 years old (44.7%), had university-level education (51.4%), and were actively employed: dependent workers (39.0%) and students (34.9%). A total of 65.7% were frequent donors. Additionally, 82.5% considered blood donation very important, 76.8% perceived benefits, and 67.7% considered the risks to be low. The main motivations were knowledge (82.6%), personal growth (68.0%), values (66.0%), and protection (62.8%). About 53.9% had a moderate level of motivation, 39.9% high, and 6.2% low. A significant association was found between age and educational level with motivation, as well as beliefs about importance, benefits, and the influence of personal beliefs. It is concluded that motivation to donate blood is mainly influenced by age, education, and positive beliefs, suggesting that campaigns should be strengthened to target young people with higher education levels and promote favorable beliefs about blood donation.